First‐Degree Living‐Related Donor Liver Transplantation in Autoimmune Liver Diseases. Issue 12 (23rd May 2016) - Aravinthan, A. D.; Doyle, A. C.; Issachar, A.; Dib, M.; Peretz, D.; Cattral, M. S.; Ghanekar, A.; McGilvray, I. D.; Selzner, M.; Greig, P. D.; Grant, D. R.; Selzner, N.; et al.
Abstract : Liver transplantation (LT) is the treatment of choice for end‐stage autoimmune liver diseases. However, the underlying disease may recur in the graft in some 20% of cases. The aim of this study is to determine whether LT using living donor grafts from first‐degree relatives results in higher rates of recurrence than grafts from more distant/unrelated donors. Two hundred sixty‐three patients, who underwent a first LT in the Toronto liver transplant program between January 2000 and March 2015 for autoimmune liver diseases, and had at least 6 months of post‐LT follow‐up, were included in this study. Of these, 72 (27%) received a graft from a first‐degree living‐related donor, 56 (21%) from a distant/unrelated living donor, and 135 (51%) from a deceased donor for primary sclerosing cholangitis (PSC) (n = 138, 52%), primary biliary cholangitis (PBC) (n = 69, 26%), autoimmune hepatitis (AIH) (n = 44, 17%), and overlap syndromes (n = 12, 5%). Recurrence occurred in 52 (20%) patients. Recurrence rates for each autoimmune liver disease were not significantly different after first‐degree living‐related, living‐unrelated, or deceased‐donor LT. Similarly, time to recurrence, recurrence‐related graft failure, graft survival, and patient survival were not significantly different between groups. In conclusion, first‐degree living‐related donor LT for PSC, PBC, or AIH is not associated with an increased risk of disease recurrence. Abstract : Recurrence, recurrence‐related graft failure, graft survival, and patient survival are similar following living‐related, living nonrelated and deceased donor liver transplantation for autoimmune liver diseases.